Dyadic coping mediates the relationship between parents' grief and dyadic adjustment following the loss of a child. Issue 1 (2nd January 2018) - Albuquerque, Sara; Narciso, Isabel; Pereira, Marco
ABSTRACT: Background and Objectives: This study aimed to examine forms of dyadic coping (DC) as mediators of the association between parents' grief response and dyadic adjustment and to determine whether these indirect effects were moderated by the child's type of death, timing of death, and age. Design: The study design was cross-sectional. Method: The sample consisted of 197 bereaved parents. Participants completed the Prolonged Grief Disorder Scale, Revised Dyadic Adjustment Scale, and Dyadic Coping Inventory. Results: Significant indirect effects of parents' grief response on dyadic adjustment were found through stress communication by oneself and by the partner, positive and negative DC by the partner, and joint DC. The timing of death moderated the association between grief response and dyadic adjustment and between joint DC and dyadic adjustment. Grief response was negatively associated with dyadic adjustment only when the death occurred after birth. Grief response was negatively associated with joint DC, which, in turn, was positively associated with dyadic adjustment, when the death occurred both before and after birth. However, the association was stronger in the latter. Conclusions: Specific forms of DC might be mechanisms through which grief response is associated with dyadic adjustment and should be promoted in clinical practice.